2019
DOI: 10.1111/febs.15035
|View full text |Cite
|
Sign up to set email alerts
|

Scavenger receptor A impairs interferon response to HBV infection by limiting TRAF3 ubiquitination through recruiting OTUB1

Abstract: The battle between hepatitis B virus (HBV) infection and the host immune defense determines the outcome of the disease. Scavenger receptor A (SRA) is a phagocytic pattern recognition receptor involved in various cellular processes, including lipid metabolism, recognition, and clearance of pathogens or modified self‐molecules. Emerging evidence pointed out that SRA might act as an immunomodulator that contributes to innate immune defense against invading pathogens. Herein, we examined the role of SRA in the ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…At the early stage of virus infection, K63-linked polyubiquitination of TRAF3 contributes to the formation of the IFN antiviral signaling complex for promoting IFN induction; however, at the late stage of virus infection, K48linked polyubiquitination of TRAF3 mediated by TRIAD3A facilitates its degradation through the ubiquitin proteasome pathway (20,49). Thus, many viruses have also employed multiple strategies to regulate the ubiquitination of TRAF3 for supporting viral replication (50)(51)(52)(53). A recent report demonstrated that K33-linked polyubiquitination of TRAF3 orchestrated the expulsion of intracellular bacteria from the TLR4 pathway (29).…”
Section: Discussionmentioning
confidence: 99%
“…At the early stage of virus infection, K63-linked polyubiquitination of TRAF3 contributes to the formation of the IFN antiviral signaling complex for promoting IFN induction; however, at the late stage of virus infection, K48linked polyubiquitination of TRAF3 mediated by TRIAD3A facilitates its degradation through the ubiquitin proteasome pathway (20,49). Thus, many viruses have also employed multiple strategies to regulate the ubiquitination of TRAF3 for supporting viral replication (50)(51)(52)(53). A recent report demonstrated that K33-linked polyubiquitination of TRAF3 orchestrated the expulsion of intracellular bacteria from the TLR4 pathway (29).…”
Section: Discussionmentioning
confidence: 99%
“…OTUB1 regulated not only cancer metastasis but also chemotherapy resistance, U Karunarathna et al had found that OTUB1 inhibited the ubiquitination and degradation of FOXM1 in breast cancer and mediated epirubicin resistance (37). Recently, some researchers had proved OTUB1 could weaken interferon response to hepatitis B virus infection (38). The effect of OTUB1 in varies tumors reminded us that OTUB1 might play important role during cancer evolution process and some physiological activities.…”
Section: Discussionmentioning
confidence: 99%
“…YOD1, which acts at a later step along the pathway to abrogate the formation of prion-like aggregates of MAVS ( 80 ), has a limited effect on IFN promotor induction at an early time point post-stimulation. In contrast, mammalian OTUB1 and USP22 were reported with opposite regulatory effects on the RLR pathway ( 67 69 , 103 , 104 ). The inhibitory effect observed after ectopic expression of the fish orthologs may be a result of the inherent bias associated with the overexpression of enzymatically-active protein, mislocalization and inadequate cell type and does not allow to distinguish the opposite functions previously described in mammals.…”
Section: Regulation By Ubiquitin Ligases and Deubiquitinasesmentioning
confidence: 94%